(untitled) (Anclajes, 2011)
This work try to observe in the contemporary Argentine political discourse the phenomena of meaning production which take place in shaping the collective memory and collective imagination. This article examines two issues: enunciative configuration and evocation. For that purpose, we use primarily analytical and theoretical categories of the social discourse theory. We based the constitution of the corpus on the referential dimension and elements organizers of the situation of enunciation. This allowed to propose two groups of texts. Through the contrasting analysis, we try to describe similarities and differences in the enunciative device performance of different groups of discourses and, simultaneously, we seek to make clearerthe current state of relations between the discourses and political positions in the contemporary field.